2012
DOI: 10.6064/2012/489208
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylglucosamine Functions in Cell Signaling

Abstract: The amino sugar N-acetylglucosamine (GlcNAc) is well known for the important structural roles that it plays at the cell surface. It is a key component of bacterial cell wall peptidoglycan, fungal cell wall chitin, and the extracellular matrix of animal cells. Interestingly, recent studies have also identified new roles for GlcNAc in cell signaling. For example, GlcNAc stimulates the human fungal pathogen Candida albicans to undergo changes in morphogenesis and expression of virulence genes. Pathogenic E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
165
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(175 citation statements)
references
References 122 publications
(210 reference statements)
9
165
1
Order By: Relevance
“…For example, GlcNAc induces hyphal growth in a diverse set of fungi (Kim et al 2000;Gilmore et al 2013), it regulates stress and virulence responses in bacteria, and it can stimulate NLRP3 inflammasome activation in mammalian cells (Konopka 2012;Wolf et al 2016). GlcNAc is commonly found at the extracellular surface of a wide range of cells as a component of bacterial peptidoglycan, fungal cell wall chitin, and mammalian cell glycosaminoglycans (Moussian 2008).…”
mentioning
confidence: 99%
“…For example, GlcNAc induces hyphal growth in a diverse set of fungi (Kim et al 2000;Gilmore et al 2013), it regulates stress and virulence responses in bacteria, and it can stimulate NLRP3 inflammasome activation in mammalian cells (Konopka 2012;Wolf et al 2016). GlcNAc is commonly found at the extracellular surface of a wide range of cells as a component of bacterial peptidoglycan, fungal cell wall chitin, and mammalian cell glycosaminoglycans (Moussian 2008).…”
mentioning
confidence: 99%
“…We also found that the hxk1Δ mutant exhibits reduced cytotoxicity compared to the wild type strain of C. albicans, which may be caused by its decreased adherence to the surface of vaginal epithelial cells ( Figures 5 -7). The human extracellular matrix contains a significant amount of GlcNAc [75]. In agreement with a recent review [75], GlcNAc released from the extracellular matrix of human cells during membrane remodeling might explain the induction of C. albicans GlcNAc catabolic genes, such as, NGT1, HXK1, NAG1, and DAC1 ( Figure 4) by vaginal epithelial cells.…”
Section: Vulvovaginal Candidiasissupporting
confidence: 83%
“…The human extracellular matrix contains a significant amount of GlcNAc [75]. In agreement with a recent review [75], GlcNAc released from the extracellular matrix of human cells during membrane remodeling might explain the induction of C. albicans GlcNAc catabolic genes, such as, NGT1, HXK1, NAG1, and DAC1 ( Figure 4) by vaginal epithelial cells.…”
Section: Vulvovaginal Candidiasissupporting
confidence: 83%
See 2 more Smart Citations